2021
DOI: 10.1007/s10198-021-01378-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-minimization analysis of immunoglobulin treatment of primary immunodeficiency diseases in Spain

Abstract: Primary immunodeficiency diseases (PID), which are comprised of over 400 genetic disorders, occur when a component of the immune system is diminished or dysfunctional. Patients with PID who require immunoglobulin (IG) replacement therapy receive intravenous IG (IVIG) or subcutaneous IG (SCIG), each of which provides equivalent efficacy. We developed a cost-minimization model to evaluate costs of IVIG versus SCIG from the Spanish National Healthcare System perspective. The base case modeled the annual cost per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…Furthermore, we also demonstrated that SCIg is more costeffective than IVIg as a form of immunoglobulin replacement for adult patients in Hong Kong. Our finding is similar to that of other cost-effective analysis studies in Australia, Canada, Iran, Spain, France, Japan and Switzerland (52)(53)(54)(55)(56)(57)(58). Projecting from the costs saved from immunodeficiency-related hospitalisation costs alone, we could potentially save HKD25,286 (USD3,221) per patient per year on SCIg compared to IVIg.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, we also demonstrated that SCIg is more costeffective than IVIg as a form of immunoglobulin replacement for adult patients in Hong Kong. Our finding is similar to that of other cost-effective analysis studies in Australia, Canada, Iran, Spain, France, Japan and Switzerland (52)(53)(54)(55)(56)(57)(58). Projecting from the costs saved from immunodeficiency-related hospitalisation costs alone, we could potentially save HKD25,286 (USD3,221) per patient per year on SCIg compared to IVIg.…”
Section: Discussionsupporting
confidence: 87%
“…An example is a cost minimization model to evaluate costs of IVIG versus SCIG from the Spanish National Healthcare System perspective, with the assumption that all IVIG infusions were administered in a hospital and 95% of SCIG infusions were administered at home. This model is similar to our system and suggests that SCIG may be a cost-saving alternative to IVIG in patients with PID [ 21 ].…”
Section: Discussionmentioning
confidence: 70%
“…The moderate savings, however, did not account for chair occupancy or nursing wages associated with IVIg hospital‐based therapy. International data from Canada, 17 the United Kingdom 18 and Spain 19 based on cost‐minimisation analysis also demonstrate considerable savings from human resources. Our study in contrast to the international data provides savings data from analysis of a cohort followed for 1 year rather than an estimate of savings based on an existing cohort.…”
Section: Discussionmentioning
confidence: 95%